The leadership during the Colony in the Tradiciones peruanas by Ricardo Palma - Lara Valladolid, Roberto Agustín (2019)
This article will analyze the traditions «Un virrey hereje y un campanero bellaco» and «La desolación de Castrovirreina». In these texts, the traditionalist proposes to demonstrate how viceroys exercised leadership during the Colony.